Emotions and Steroid Secretion in Aging Men: A Multi—Study Report - Walther, Andreas; Waldvogel, Patricia; Noser, Emilou; Ruppen, Jessica; Ehlert, Ulrike (Frontiers in Psychology, 2017)
Although aging increases the risk of cognitive and socioemotional deterioration, it has also been shown to be accompanied by an increase in experienced positive emotions and a decrease in negative emotions. Steroid hormones and age-related alterations in secretion patterns have been suggested to play a crucial role in these age-related changes in emotional experience. Importantly, previous studies identified effects of neuroactive hormones on age-related alterations in emotional experience, which vary by sex and depression levels. Therefore, in three independent cross-sectional studies including a total of 776 men, we examined age-related differences in emotional experience and subsequently the moderation effect of steroid hormones. Sample one consisted of 271 self-reporting healthy (SRH) men aged between 40 and 75 years, while sample two comprised 121 men in the identical age range but only including vitally exhausted (VE) men. Sample three included 384 men aged between 25 and 78 years who reported having fathered (FA) at least one child. For the SRH men, age was negatively associated with anxiety symptoms and aggression, while negative trends emerged for depressive symptoms. In VE men, age was negatively associated with depressive symptoms and positively associated with aggression and positive emotions. For FA men, anxiety symptoms and aggression were negatively associated with age. Age trends of steroid hormones and identified moderation effects are reported. However, with adjustment for multiple comparisons, most of the significant associations fade and the reported associations need to be regarded as exploratory starting points for the further investigation of age-related alterations in emotional experience and their relation to steroid secretion. Overall, the results indicate that salivary cortisol might be a moderator of the association between age and symptoms of anxiety for SRH and VE men, while salivary testosterone seems to moderate the association between age and symptoms of anxiety or depression in VE and FA men, respectively. Both hair cortisol and progesterone seem to influence age-related alterations in anger experience. Age-related alterations in the hypothalamic-pituitary-adrenal (HPA) axis and the hypothalamic-pituitary-gonadal (HPG) axis emerge as promising avenues to further investigate the decrease in experienced negative emotions in aging men.